The Influence of Health Awareness and Product Knowledge on Intention to Purchase Lemonilo Instant Noodle Products Mediated by Attitude in Pekanbaru City - Deni, Normala; Wijayanto, Gatot; Nursanti, Aida (CV. Rayyan Dwi Bharata, 2024)
This research aims to determine the influence of health awareness and product knowledge on intention to buy Lemonilo Instant Noodle products, which is mediated by attitudes in Pekanbaru City. The research was conducted on the people of Pekanbaru City who know and understand the Lemonilo Instant Noodle product by distributing questionnaires to 140 respondents as a sample. The sampling technique used in this research is non-probability sampling with Purposive Sampling technique. The data analysis technique uses the Structural Equation Modeling (SEM) method with Partial Least Squares (PLS) using Smart-PLS Software version 3.2.9. The research results show that health awareness and product knowledge have a significant effect on attitudes towards Lemonilo Instant Noodle products in Pekanbaru City. Health awareness, product knowledge and attitudes have a significant influence on interest in purchasing Lemonilo Instant Noodle products in Pekanbaru City. Health awareness and product knowledge have a significant effect on intention to buy Lemonilo Instant Noodle products, which is mediated by attitude in Pekanbaru City.